A DEEPER LOOK INTO RURAL ENGLISH TEACHERSâ BELIEFS ABOUT ENGLISH - Hidayati, Nurun (Universitas Muhammadiyah Surakarta, 2017)
The research aimed at finding out two questions: 1). what are rural English teachersâ beliefs about English in a rural school in facing the modern era?; and2). to what extent is English important in a rural school related to its global role viewed from teachersâ belief?. This paper utilized qualitative method in the form of case study. The respondents of the study were three English teachers from a rural school. The data were gathered through observation and interview then analyzed through the interactive model which consists of data reduction, data display, and conclusion: drawing/verification. The data analyzed reveals that: 1). English is crucially needed in rural school to develop human resources and to lead students to get the latest information; 2). English takes the global role in the rural school for helping students to learn internet and computer, to balance human resources and natural resources and as a foundation for making the connection with other people around the world in the wider scope. At the end of the paper, suggestions, and recommendation were also provided.Â Keywords: teachersâ beliefs, rural school, the importance of English